Making the most of your placement - Neugebauer, John.; Evans-Brain, Jane.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
'Making The Most Of Your Placement' is an essential source of support and guidance for undergraduate students doing work placements or summer internships as part of their degree course.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Internship programs -- Great Britain; Business -- Vocational guidance -- Great Britain; Vocational education -- Great Britain; Electronic books